Fuzzy Logic Expert System In Student Behavior Throwing Waste - Sanny; Fauzi, Rezki (Journal of Computer Science and Informatics Engineering, 2023)
School as a facility for the nation’s generation to be competitive and ready to build the nation with the expertise they have. Student behavior that is formed will certainly have an impact on the sustainability of the facilities available at school, where this is a reflection of how students behave outside of school. For this reason, the application of penalties for students who violate should be applied fairly and properly. With the design of expert system-based applications and studies based on fuzzy logic, it is hoped that schools can use it in imposing penalties and the number of mistakes made by students who litter. In this study, it was seen how the role of students towards the environment in managing waste, especially in the school environment. The results of the rule are determined as future reference criteria for changing the behavior of students who are aware of better waste management.